Network Pharmacology and Molecular Docking Study of the Chinese Miao Medicine Sidaxue in the Treatment of Rheumatoid Arthritis - Wu N; Yuan T; Yin Z; Yuan X; Sun J; Wu Z; Zhang Q; Redshaw C; Yang S; Dai X (Dove Medical Press, 2022)
Ning Wu,1,* Taohua Yuan,1,* ZhiXin Yin,1 Xiaotian Yuan,1 Jianfei Sun,1 Zunqiu Wu,1 Qilong Zhang,1 Carl Redshaw,2 Shenggang Yang,1 Xiaotian Dai3 1Guizhou Medical University, Guiyang, Guizhou, People's Republic of China; 2Department of Chemistry, University of Hull, Hull, Yorkshire, HU6 7RX, UK; 3Department of Mathematics and Statistics, University of Calgary, Calgary, AB, Canada*These authors contributed equally to this workCorrespondence: Shenggang Yang, Guizhou Medical University, Guiyang, Guizhou, 550025, People's Republic of China, Tel/Fax +86 13158000576, Email yangshenggang2021@126.com Xiaotian Dai, Department of Mathematics and Statistics, University of Calgary, Calgary, AB, T2N 1N4, Canada, Tel/Fax +1 435 754 4980, Email xiaotian.dai@uCalgary.caPurpose: This study aimed to investigate the molecular mechanisms of Compound Sidaxue (SX), a prescription of Chinese Miao medicine, in treating rheumatoid arthritis (RA) using network pharmacology and in vivo experimental approaches.Methods: Network pharmacology was adopted to detect the active components of four Traditional Chinese herbal medicine (TCM) of SX, and the key targets and signaling pathways in the treatment of RA were predicted, and the key components and targets were screened for molecular docking. The predicted targets and pathways were validated in bovine type II collagen and incomplete Freund's adjuvant emulsifier-induced rat RA model.Results: In this study, we identified 33 active components from SX, predicted to act on 44 RA-associated targets by network pharmacology. PPI network demonstrated that TNF-α, VEGF-A, IL-2, IL-6, AKT, PI3K, STAT1 may serve as the key targets of SX for the treatment of RA. The main functional pathways involving these key targets include PI3K-AKT signaling pathway, TNF signaling pathway, NF-κB signaling pathway. Molecular docking analysis found that the active components β-amyrin, cajanin, eleutheroside A have high affinity for TNF-α, VEGFA, IL-2, AKT, and PI3K, etc. SX can improve joint swelling in Collagen-induced arthritis (CIA) rats, reduce inflammatory cell infiltration and angiogenesis in joint synovial tissue, and down-regulate IL-2, IL-6, TNF-α, VEGF, PI3K, AKT, p-AKT, NF-κBp65, the expression of p-NF-κBp65, STAT1, and PTGS2 are used to control the exacerbation of inflammation and alleviate the proliferation of synovial pannus, and at the same time play the role of cartilage protection to achieve the effect of treating RA.Conclusion: Through a network pharmacology approach and animal study, we predicted and validated the active compounds of SX and their potential targets for RA treatment. The results suggest that SX can markedly alleviate CIA rat by modulating the VEGF/PI3K/AKT signaling pathway, TNF-α signaling pathway, IL/NF-κB signaling pathway.Keywords: network pharmacology, molecular docking, rheumatoid arthritis, Sidaxue, VEGF/PI3K/AKT signaling pathway, TNF-α signaling pathway, IL/NF-κB signaling pathway